EFEKTIFITAS PENAMBAHAN TERAPI PENGUATAN OTOT PEKTORALIS MAYOR DAN MINOR PADA MASASE PAYUDARA TERHADAP PRODUKSI ASI IBU NIFAS - Intarti, Wiwit Desi; Hesti Savitri, Naomi Parmila (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Effectiveness of additional strengthening pectoralis muscle therapy major and minor in breast massage postpartum mother of production breast milk. Breast milk is the best food for infants, exclusive breastfeeding will result in a decrease infant morbidity and even mortality. ASI has a high content of protein hormone known as adiponection which can reduce the risk of disease - a disease in infants and toddlers. Rapid milk production required knowledge of techniques - techniques that support to facilitate the production of breast milk. Some of the factors that influence milk production among other nutritional factors, psychology, rest and stimulant factor. The purpose of this study was to examine the effectiveness of the addition of strengthening therapy pectoralis major and minor muscles in the breast massase on milk production postpartum mothers.Quasi Experimental Research models using the design in this study was a cross sectional study design is that measurements and observations conducted simultaneously at one time (one time) with a case-control study design. Population of this research is the post partum mothers in hospitals Dr. M.Ashari Pemalang. Samples to be used as the unit of analysis by using purposive sampling technique that type of judgment sampling as many as 35 respondents. Menggunanakan research instrument checklist and observation sheet strengthening therapy and minor pectoralis major muscle and breast massase with t-test related. T-test results related to the level of 95% t value 5837> t table 2021 on the right breast, and t value 5,034> t table 2,021 on the left breast. Then Ho is rejected and Ha accepted. Conclusions are strengthening the effectiveness of the therapy the addition of the pectoralis major and minor muscles in the breast massage for milk production. Keywords: the addition of strengthening minor pectoralis major muscle, breast massage, production breast milk